Effects of garlic (Allium sativum L) and Citrullus colocynthis (L.) Schrad individually and in combination on male reproductive damage due to diabetes: suppression of the AGEs/RAGE/Nox-4 signaling pathway - Aghileh Mohammadzadeh; Ali Gol; Reza Kheirandish (BMC, 2024)
Abstract Background Diabetes Mellitus is associated with disturbances in male reproductive function and fertility. Studies have shown that oxidative stress with the subsequent inflammation and apoptosis cause these complications in diabetes. Garlic (G) (Allium sativum L) and Citrullus colocynthis (L.) Schrad (C) both have antidiabetic and antioxidant properties. Recently, we demonstrated their synergistic effects in alleviating reproductive complications when administered concomitantly. However, as even medicinal plants in long term usage may lead to some unwanted side effects of their own, we examined whether with half the original doses of these two medicinal plants we could achieve the desired results. Methods Thirty-five male Wistar rats were divided into five groups (n = 7/group): Control, Diabetic, Diabetic + G (0.5 ml/100 g BW), Diabetic + C (5 mg/kg BW) and Diabetic + GC (0.5 ml/100 g BW of garlic and 5 mg/kg BW of C. colocynthis) groups. The experimental period was 30 days. Results Oxidative stress, advanced glycation end products (AGEs), immunoexpression of caspase-3, and expression of mRNAs for receptor for advanced glycation end products (RAGE), NADPH oxidase-4 (NOX-4) and nuclear factor kappa B increased in testis of diabetic rats. Treatment with garlic and C. colocynthis alone showed some beneficial effects, but in the combination form the effectiveness was more profound. Conclusions We conclude that the combination therapy of diabetic rats with lower doses is still as efficient as higher doses; therefore, the way forward for reducing complications in long term consumption.